2023
DOI: 10.1002/jev2.12303
|View full text |Cite
|
Sign up to set email alerts
|

Faeces‐derived extracellular vesicles participate in the onset of barrier dysfunction leading to liver diseases

Abstract: The role of extracellular vesicles (EVs) from faeces (fEVs) and small circulating EVs (cEVs) in liver diseases such as non‐alcoholic fatty diseases (NAFLD) and non‐alcoholic steatohepatitis (NASH) has not been demonstrated. fEVs and cEVs of healthy donors, NAFLD and NASH patients were isolated and characterized. The effects of EVs were evaluated in intestinal, endothelial, Kupffer and stellate cells. Non‐muscular myosin light chain kinase (nmMLCK) deficient mice were used in vivo. Bacterial origins of fEVs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…This positive relationship between uric acid and intestinal permeability, previously demonstrated in our study ( Lv et al, 2020 ), was consistently observed throughout hyperuricemia. Intestinal barrier dysfunction is believed to be a significant driver of metabolic syndrome, as pathogenic microbes and their products can access the systemic circulation through a compromised barrier, migrate to inflamed sites, and directly contribute to inflammation in key metabolic tissues, ultimately promoting metabolic inflammation and exacerbating metabolic disturbances ( Fizanne et al, 2023 ; Violi et al, 2023 ). Given these findings, targeting the intestinal barrier presents an attractive approach for mitigating the metabolic dysfunctions associated with hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…This positive relationship between uric acid and intestinal permeability, previously demonstrated in our study ( Lv et al, 2020 ), was consistently observed throughout hyperuricemia. Intestinal barrier dysfunction is believed to be a significant driver of metabolic syndrome, as pathogenic microbes and their products can access the systemic circulation through a compromised barrier, migrate to inflamed sites, and directly contribute to inflammation in key metabolic tissues, ultimately promoting metabolic inflammation and exacerbating metabolic disturbances ( Fizanne et al, 2023 ; Violi et al, 2023 ). Given these findings, targeting the intestinal barrier presents an attractive approach for mitigating the metabolic dysfunctions associated with hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…Outer membrane vesicles are derived from the outer membrane of Gram-negative bacteria carrying material from periplasmic and cytoplasmic components ( Toyofuku et al, 2019 ). Bacterial extracellular vesicles are the language of communication between bacteria and hosts, and can be used to regulate a variety of biological functions including biofilm formation, alteration of small intestinal epithelial permeability ( Fizanne et al, 2023 ), increase in host angiogenesis and osteogenesis ( Chen et al, 2022 ), inhibition of host viral infections and host collaboration in viral clearance ( Ñahui Palomino et al, 2019 ; Bhar et al, 2022 ), induction of host resistance to other bacteria ( Zhou et al, 2023 ), and host immunomodulation ( Xie et al, 2022 ). Bacterial extracellular vesicles can release the contents of bacterial extracellular vesicles into host cells through three ways: endocytosis, internalization of bacterial extracellular vesicles through lipid rafts, and direct membrane fusion ( Ñahui Palomino et al, 2021 ).…”
Section: Drug Delivery Systems and Factors Affecting Transdermal Drug...mentioning
confidence: 99%
“…EVs from gram‐negative periodontal pathogens ( P. gingivalis and Tannerella forsythia ) also have immunostimulatory activities through TLR2 activation (Kim et al., 2022 ). Recently, a study of the link between NAFLD/NASH and bacterial extracellular vesicles was reported (Fizanne et al., 2023 ). Faeces EVs and blood circulating EVs from NAFLD/NASH patients contain higher amounts of LPS than those from healthy subjects, and only faeces‐derived EVs from NASH patients contain lipoteichoic acid (LTA), which is one of the TLR2 ligands of gram‐positive bacteria.…”
Section: Introductionmentioning
confidence: 99%